Review of Learning strategy instruction in the language classroom: Issues and implementation; Editors: Anna Uhl Chamot, Vee Harris; Publisher: Multilingual Matters, 2019; ISBN: 9781788923392; Pages: 296 - Trendak, Olga (Studies in Second Language Learning and Teaching, 2019)
The book Learning Strategy Instruction in the Language Classroom: Issues and Implementation, edited by Anna Uhl Chamot and Vee Harris, touches upon crucial issues pertaining to language learning strategies (LLS) and language learning strategy instruction (LLSI), both from a theoretical and practical perspective. All the contributors to the volume are specialists with considerable expertise in the field of LLS and LLSI, which makes the book an informative and inspirational read. The authors look at the concept of strategy instruction from different perspectives, meticulously not only investigating various LLSI models, taking account of “learner needs and settings and particular language skills,” but also “considering curricula, materials, teachers roles, the ways in which scaffolding is enacted in the classrooms” (p. viii). Since the volume adeptly combines research into LLSI with its theoretical aspects and complexities, it will prove useful to practitioners and researchers alike. Delineating new directions in the field of LLSI, the edited collection is undoubtedly a valuable contribution to ongoing discussions about LLSI and its implementation in the classroom.